Anti‐infective immunoadhesins from plants. Issue 8 (4th August 2015) - Wycoff, Keith; Maclean, James; Belle, Archana; Yu, Lloyd; Tran, Y; Roy, Chad; Hayden, Frederick
Summary Immunoadhesins are recombinant proteins that combine the ligand‐binding region of a receptor or adhesion molecule with immunoglobulin constant domains. All FDA‐approved immunoadhesins are designed to modulate the interaction of a human receptor with its normal ligand, such as Etanercept (Enbrel®), which interferes with the binding of tumour necrosis factor (TNF) to the TNF‐alpha receptor and is used to treat inflammatory diseases such as rheumatoid arthritis. Like antibodies, immunoadhesins have long circulating half‐lives, are readily purified by affinity‐based methods and have the avidity advantages conferred by bivalency. Immunoadhesins that incorporate normal cellular receptors for viruses or bacterial toxins hold great, but as yet unrealized, potential for treating infectious disease. As decoy receptors, immunoadhesins have potential advantages over pathogen‐targeted monoclonal antibodies. Planet Biotechnology has specialized in developing anti‐infective immunoadhesins using plant expression systems. An immunoadhesin incorporating the cellular receptor for anthrax toxin, CMG2, potently blocks toxin activity in vitro and protects animals against inhalational anthrax. An immunoadhesin based on the receptor for human rhinovirus, ICAM‐1, potently blocks infection of human cells by one of the major causes of the common cold. An immunoadhesin targeting the MERS coronavirus is in an early stage of development. We describe here the unique challenges involved in designing and developing immunoadhesins targeting infectious diseases in the hope of inspiring further research into this promising class of drugs.